CircRNA hsa_circ_0004585 as a potential biomarker for colorectal cancer - Tian, Jinhai (Cancer Manag Res, 2019)
Objective: Circular RNAs (circRNAs) are involved in regulating of carcinogenesis of various cancer cells. However, the function of circRNAs in colorectal cancer (CRC) has remained largely unknown. This study investigated the characteristic expression of circRNAs in CRC and adjacent normal tissues, analyzed the miRNAs related to candidate circRNAs, and studied the correlation between circRNAs with clinical data of CRC. Methods: Human CircRNA microarray has been applied to screen the expressions of circRNAs of the CRC tissues and adjacent normal tissues. Quantitative real-time polymerase chain reaction (qRT-PCR) verified the candidate circRNAs in CRC tissue and patients’ peripheral blood. The circRNA array data were analyzed by GeneSpring 13.0 (Agilent) software. The diseases, pathways and functional enrichment analysis of these genes were performed using the KEGG system. In addition, the circRNA-miRNA network was constructed based on the miRanda-3.3 software. Statistical analysis was performed with SPSS23.0, GraphPad Prism, and Sigmaplot software. Results: In total, 13,198 circRNAs were identified as distinct between CRC and adjacent normal tissues, including 6,697 upregulated and 6,501 downregulated genes. Based on scores, six of them were selected for further verification in CRC tissues and peripheral blood. The hsa_circ_0004585 expression was significantly upregulated both in CRC patients tissue and peripheral blood. Hsa_circ_0004585 was positively correlated with patient’s tumor size, indicating the function of hsa_circ_0004585 in CRC carcinogenesis and metastasis. Conclusion: Hsa_circ_0004585 could be a potential biomarker for diagnosis of CRC.